2014
DOI: 10.1371/journal.pone.0103603
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Liver Fibrosis by Intrasplenic Injection of High-Density Cultured Bone Marrow Cells in a Rat Chronic Liver Injury Model

Abstract: Endothelial progenitor cells (EPCs) from bone marrow have proven to be functional for the prevention of liver fibrosis in chronic liver injury. However, expansion of EPCs in culture is complicated and expansive. Previously, we have established a simple method that could enrich and expand EPCs by simple seeding bone marrow cells in high density dots. The purpose of this study is to evaluate whether cells derived from high-density (HD) culture of rat bone marrow cells could prevent the liver fibrosis in a chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…In another study, infusion of enriched population of EPCs in 6 week‐CCl 4 treated rats has shown anti‐fibrogenic effect of the cells in terms of biochemical and histological evidences. However, the study has failed to observe any differentiation of transplanted cells into hepatocytes or endothelial cells, indicating that the donor cells function mainly through a paracrine effects to prevent liver fibrosis and regeneration, rather than by direct differentiation . In the present study, we observed GFP‐EPCs around LSECs during the 4th week of CCl 4 treatment.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In another study, infusion of enriched population of EPCs in 6 week‐CCl 4 treated rats has shown anti‐fibrogenic effect of the cells in terms of biochemical and histological evidences. However, the study has failed to observe any differentiation of transplanted cells into hepatocytes or endothelial cells, indicating that the donor cells function mainly through a paracrine effects to prevent liver fibrosis and regeneration, rather than by direct differentiation . In the present study, we observed GFP‐EPCs around LSECs during the 4th week of CCl 4 treatment.…”
Section: Discussioncontrasting
confidence: 57%
“…These results suggest that EPCs contributes little towards endothelial regeneration during liver injury. It has been earlier shown that the intraperitoneal administration of EPCs into rat model of liver injury by CCl 4 enhances liver regeneration and suppresses liver fibrogenesis . In the above study, Liu et al.…”
Section: Discussionmentioning
confidence: 87%
“…Even a small increase in the number of endothelial cells during fibrosis, as observed in our results after cell therapy, could have an important role in tissue remodeling. However, these cells are also associated with tissue tumorigenesis and metastasis, and it is noteworthy that only when healthy animals were injected with BMC, endothelial progenitor cells percentage was highly increased, suggesting that the safety of BMC transplantation is associated with the presence of a chronic liver injury in our model [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many stem cell types, such as HSCs [ 4 ], BM stem cells [ 6 , 7 , 11 , 23 25 , 27 , 33 35 ], and adipose-derived stem cells [ 36 40 ], have been investigated for liver transplantation and treatment of end-stage liver disease (ESLD). Although recent studies have shown positive effects of stem cell therapy in ESLD treatment, there are controversies regarding the source of stem cells and administration strategies.…”
Section: Discussionmentioning
confidence: 99%